2008
DOI: 10.1097/phm.0b013e31818de070
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and Medical Management of the Adult with Spina Bifida

Abstract: .As the life expectancy of individuals with spina bifida increases, a lifelong need for management of many health issues in a rehabilitation setting has emerged in recent years. Physiatrists, in consultation with a variety of adult specialists, are particularly well suited to manage the common musculoskeletal, skin, bowel, bladder, renal, neurological, and other issues that arise in the adult population. This article reviews the last 20 yrs of literature pertinent to the rehabilitative care of this population,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
114
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 277 publications
3
114
0
3
Order By: Relevance
“…Rehabilitative and supportive care needs are frequently experienced by pwSB many years after initial treatment [11,12]. In this study many participants reported ongoing transient and/or persistent physical and psychosocial morbidity such as bowel and/or urinary dysfunction and psychosocial issues, consistent with other reports [28,31,32].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Rehabilitative and supportive care needs are frequently experienced by pwSB many years after initial treatment [11,12]. In this study many participants reported ongoing transient and/or persistent physical and psychosocial morbidity such as bowel and/or urinary dysfunction and psychosocial issues, consistent with other reports [28,31,32].…”
Section: Discussionsupporting
confidence: 78%
“…Although several studies in the paediatric population demonstrate effectiveness of a coordinated ID approach to management, this does not extend to adults and there is lack of comprehensive ambulatory care models [11][12][13]. The aim of this study, therefore, was to assess the effectiveness of a structured ID rehabilitation intervention to improve disability and participation in an adult SB population in an Australian community cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Dicianno and colleagues demonstrated that a multidisciplinary dedicated spina bifida team provides optimal care for children. 10 However, far fewer comprehensive adult spina bifida clinics exist. 10 As spina bifida patients age, they present a variety of unique challenges.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, far fewer comprehensive adult spina bifida clinics exist. 10 As spina bifida patients age, they present a variety of unique challenges. For instance, a recent systematic review found total continence in this population to be only 37.7%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation